Fabrication and characterization of ion-imprinted polymer for removal of mercury - Ab. Rahman, Siti Khadijah (2017)
Mercury (Hg) is a natural trace component found in the petroleum reservoir. The presence of Hg is detrimental to petroleum production facilities as it forms corrosion induced through Hg amalgamates. Moreover, it has an effect on human beings if it is discharged into the waterways and atmosphere leading to severe, acute and chronic poisoning. Ion imprinted polymer (IIP) being one of the latest adsorbents which is alternative technique that is more selective and effective than the conventional removal method of Hg. IIP is synthetic polymers having a predetermined selectivity for a template ion, which makes them ideal materials to be used in removal processes. In this study, the IIP was developed for the removal of Hg(II) ions from aqueous solutions and actual samples. The IIP particles and monoliths was prepared by thermal polymerization technique with Hg(II) as a template ions, [2-(methacryloyloxy)ethyl] trimethylammonium cysteine (MAETC) as a ligand, methacrylic acid (MAA) as a functional monomer, 2-hydroxyethyl methacrylate ethylene glycol (HEMA) as a co-monomer, dimethacrylamide (EGDMA) as a cross-linker, benzoyl peroxide (BPO) as an initiator and methanol or acetonitrile as a porogen. The IIP-20A monolith was selected as the best monolithic IIP due to its high adsorption capacity and good physical properties. The prepared IIP-particle and all of the monolithic IIPs were characterized using Fourier transform infrared (FTIR), thermal gravimetric analysis (TGA), field emission scanning electron microscope (FESEM) and Brunauer Emmet-Teller (BET) for determining the polymerization and imprinting process occurred. In the down-flow technique of IIP-20A monolith, pH, dosage, initial concentration, reusability, selectivity and kinetic study were investigated. Removal of Hg(II) of pH dependent was found maximum at pH 4.7. The removal percentage of Hg(II) increased with increasing of adsorbent dose and the total uptake of Hg(II) increased with increasing initial concentration of Hg(II) ions.The kinetic study of Hg(II) adsorption by IIP-20A monolith was fit well with Adam’s Bohart model. The adsorbents have very good selectivity towards Hg(II) ions even in the presence of other metals (Pb(II), Cd(II), As(II) and Cr(III)) and can be reusable up to fifteen cycles. The comparison of removal test of Hg(II) ions for up-flow column technique (pilot plant-scale) showed that the IIP-20A monolith having good adsorption capacities compared with IIP-particle (packed in a coffee filter). Other than that, the IIP-20A monolith has been successfully applied for the recovery of trace Hg(II) in actual samples (river water, wastewater and condensate).